First and second dorsal metacarpal artery free flap in a degloving case - Galván, Santos Enrique Platas; García Gutiérrez, Gladys Esthela; Ocampo, Rafael Reynoso; Ramirez, José Bruno Mendoza; Desentis, Alfonso Echeverría (International Journal of Research in Medical Sciences, 2025)
Digital degloving injuries are uncommon but represent a significant challenge in hand surgery due to the circumferential loss of coverage, bone exposure, and functional compromise. Although multiple reconstructive options have been described, none has become the gold standard, and in many cases the outcome ends in amputation. We report a 55-year-old male patient with a circumferential degloving injury of the left index finger, showing complete bone exposure of the middle and distal phalanges and partial exposure of the proximal phalanx. Surgical management consisted of debridement and resection of necrotic tissue, followed by reconstruction using two synchronous contralateral free Kite flaps to cover the dorsal and volar surfaces, in addition to a full-thickness skin graft to the residual radial wound. Postoperative evolution was satisfactory, with 90% graft integration and complete flap viability. At six months, the donor site exhibited full healing, preserved mobility, intact pinch function, and no residual pain. The synchronous use of double free Kite flaps constitutes an innovative, anatomically faithful, and low-morbidity alternative for managing circumferential digital injuries. This case expands the clinical spectrum of the kite flap and suggests new possibilities for application in complex microsurgical hand reconstruction.